If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10z + -1z = -3 + 6z + -2 + -4 Combine like terms: 10z + -1z = 9z 9z = -3 + 6z + -2 + -4 Reorder the terms: 9z = -3 + -2 + -4 + 6z Combine like terms: -3 + -2 = -5 9z = -5 + -4 + 6z Combine like terms: -5 + -4 = -9 9z = -9 + 6z Solving 9z = -9 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. 9z + -6z = -9 + 6z + -6z Combine like terms: 9z + -6z = 3z 3z = -9 + 6z + -6z Combine like terms: 6z + -6z = 0 3z = -9 + 0 3z = -9 Divide each side by '3'. z = -3 Simplifying z = -3
| sqrt(x+13)+sqrt(x+45)=8 | | x^2+23x=1674 | | (c-4d)(2c-d)= | | 10(c-4)+9=8+c-39 | | 40=6x | | 127.61=2.35h+73.56 | | -24+3k=k-4k | | (x+4)(x+4i)(x-4i)=0 | | -4x-11=6x+19 | | 1-2(x+2)=-9x-17 | | 18y-14y=16 | | P-5*p-5= | | 3(x-3)+8x=68 | | -4(7x-1)+2=28x+6 | | -0.5=6 | | 5x+7=2x+55 | | -(2-5b)=16b+20 | | 5x+7=2x-55 | | 5y+7=4y-7 | | 15-7+12+20=x-7x-8x | | x+13+x+45=8 | | 4(x-1)=-2x-4 | | 24(1020)= | | 7+3(x-4)+8x= | | -4x(x-4)-28=-12 | | 5(3x-15)=15x(x-15) | | -6(v+4)+4v+6=7v+10 | | 116-x+49=x+91 | | 41(502)= | | 12x-30=6(x-1) | | -10d-18d+-10+-13=7 | | 2r-(r-5)=13+2r |